2001
DOI: 10.1123/ijsnem.11.1.53
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Potassium Phosphate Supplementation on Perceptual and Physiological Responses to Maximal Graded Exercise

Abstract: This investigation evaluated the effect of oral potassium phosphate supplementation on ratings of perceived exertion (RPE) and physiological responses during maximal graded exercise tests (GXT). Eight highly trained endurance runners completed a GXT to anchor the Borg 15-point RPE scale and two double-blind counterbalanced GXTs. Subjects ingested either 4,000 mg x day(-1) of phosphate (PHOS) or a placebo (PLA) for 2 days. Two weeks separated GXTs. Phosphate levels obtained immediately prior to the GXTs were gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…An older study comparing two days of potassium phosphate (PP) loading (4 g·day −1 ) to placebo in highly-trained endurance runners (crossover n = 8) showed that PP may reduce the rate of perceived exertion (RPE) during the mid-stages of maximal treadmill running, although no changes in physiological parameters were identified. This may be due to the short loading phase [134]. Others have shown that SP loading (4 g) over three days improved VO 2peak in elite endurance athletes by ~9%, increased blood haematocrit levels, glucose and other markers of metabolic demand [135].…”
Section: Discussionmentioning
confidence: 99%
“…An older study comparing two days of potassium phosphate (PP) loading (4 g·day −1 ) to placebo in highly-trained endurance runners (crossover n = 8) showed that PP may reduce the rate of perceived exertion (RPE) during the mid-stages of maximal treadmill running, although no changes in physiological parameters were identified. This may be due to the short loading phase [134]. Others have shown that SP loading (4 g) over three days improved VO 2peak in elite endurance athletes by ~9%, increased blood haematocrit levels, glucose and other markers of metabolic demand [135].…”
Section: Discussionmentioning
confidence: 99%
“…This number was determined using a G-power analysis (Faul, Erdfekder, Buchner, & Lang, 2009), based on an effect size of 1.1 (Goss et al, 2001), with an alpha level of 0.05% and 85% power. Participants were not taking any nutritional supplements for at least 2 months prior to or during this study.…”
Section: Participantsmentioning
confidence: 99%
“…However, in the case of repeated sprints, the magnitude of benefit has been shown to be varied and unclear (Kopec et al, 2016). Finally, there is also a large amount of contrary evidence from the same physiological and performance measures that suggests phosphate supplementation (in isolation, or in combination with other buffer agents) has no impact on exercise capacity or performance outcomes (Brewer et al, 2014;Goss et al, 2001;Kraemer et al, 1995;West et al, 2012). No doubt, the lack of clear consensus defined by this collective work is explained by variations in the supplement protocol used (i.e., differences in dose, type, exercise protocol, etc.)…”
Section: Phosphatesmentioning
confidence: 99%